The Covid-19 Pandemic and Its Implications in Islamic Religious Education Learning at Junior High School (SMP) of Ma'arif 9 Seputih Banyak Central Lampung: Array (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2022)
Covid-19 has had an effect on every area of ​​Indonesian society's life, one of which is the world of education. The implication is to make the learning process into distance learning, inevitably it must be implemented considering the Ministry of Education and Culture's instructions to continue learning in the midst of the Covid-19 outbreak. Teachers at all levels of education are required to make new learning plans related to Distance Learning (PJJ), which had never been implemented before. From this explanation, the formulation of the problem is 1. How is distance learning applied during the Covid-19 period in improving the learning process of Islamic Religious Education at Ma'arif 9 Seputih Banyak Middle School, Central Lampung? 2. What are the inhibiting and supporting factors for the implementation of learning in improving the learning process of Islamic Religious Education at SMP Ma'arif 9 Seputih Banyak, Central Lampung? 3. What are the implications of the COVID-19 pandemic on Islamic Religious Education learning at SMP Ma'arif 9 as white as many, Central Lamongan. The research method used is descriptive qualitative. Meanwhile, the data sources are school principals, waka curriculum and Islamic Religious Education teachers, students. In collecting the required data, the authors use the methods of observation, interviews, and documentation. The results of the research that the author got were that the application of distance learning during the Covid-19 period in improving the learning process of Islamic Religious Education at SMP Ma'arif 9 Seputih Banyak, Central Lampung went well and could be implemented as it should